Gene expression and locomotor recovery in adult rats with spinal cord injury and plasma-synthesized polypyrrole/iodine application combined with a mixed rehabilitation scheme - Coyoy-Salgado, Angélica; Orozco-Barrios, Carlos; Sánchez-Torres, Stephanie; Olayo, María Guadalupe; Cruz, Guillermo Jesus; Morales-Corona, Juan; Olayo, Roberto; Diaz-Ruiz, Araceli; Ríos, Camilo; Alvarez-Mejia, Laura; Mondragón-Lozano, Rodrigo; Morales-Guadarrama, Axayacatl; et al. (Frontiers in Neurology, 2023)
Spinal cord injury (SCI) can cause paralysis, for which effective therapeutic strategies have not been developed yet. The only strategy accepted for patients is rehabilitation (RB), although this does not allow complete recovery of lost functions, which makes it necessary to combine it with strategies like plasma-synthesized polypyrrole/iodine (PPy/I), a biopolymer with different physicochemical properties than the PPy synthesized by conventional methods. After SCI in rats, PPy/I promotes functional recovery. So the purpose of this study was to increase the beneficial effects of both strategies and identify which genes activate PPy/I applied alone or in combination with a mixed scheme of RB by swimming and enriched environment (SW/EE) in rats with SCI. Microarray analysis was performed to identify mechanisms of action that underlying the effects of PPy/I and PPy/I+SW/EE in motor function recovery evaluated by BBB scale. Results showed robust up regulation by PPy/I in genes related to developmental process, biogenesis, synapse, and synaptic vesicle trafficking. Besides PPy/I+SW/EE increased the expression of genes related to proliferation, biogenesis, cell development, morphogenesis, cell differentiation, neurogenesis, neuron development and synapse formation processes. Immunofluorescence analysis showed expression of β-III tubulin in all groups, a decreased expression of caspase-3 in PPy/I group and of GFAP in PPy/I+SW/EE group (p<0.05). Better preservation of nerve tissue was observed in PPy/I and PPy/SW/EE groups (p<0.05). In BBB scale, control group scored 1.72±0.41, animals with PPy/I treatment scored 4.23±0.33, and those with PPy/I+SW/EE scored 9.13±0.43 one month after follow-up. So, PPy/I+SW/EE could represent a therapeutic alternative for motor function recovery after SCI.